Double-pass pumped extracavity optical parametric oscillator with passive optical feedback suppression. (10th March 2016) - Alyamani, A; Algahtani, M; Rusak, A A; Orlovich, V A; Dashkevich, V I; El-Desouki, M
Abstract: We demonstrate a simple way of building a compact eye-safe laser source based on a double-pass pumped extracavity optical parametric oscillator (EOPO) without an optical Faraday isolator. A Nd:KGW pump laser (PL) and the KTP EOPO located close to the PL are designed with stable cavities, while the 100% end system mirrors form an unstable cavity with sufficiently high threshold at 1067 nm. At the 6.6 J pump of the Nd:KGW laser, the EOPO output energy obtained at 1577 nm is 14.7 mJ, corresponding to the conversion efficiency of 33% with respect to the fundamental. The pulse width is 7 ns and the output beam divergence is 3 times diffraction limit.